Reliabilitas dan validitas dari modified dental anxiety scale dalam versi Bahasa Indonesia (Reliability and validity of modified dental anxiety scale in the Indonesian version) - Fitrian Riksavianti; Rasmidar Samad (Journal of Dentomaxillofacial Science, 2014)
Questionnaire of modified dental anxiety scale (MDAS) have been translated into various languages such as Spain,Greece, China, Romania, Turkey and Malaysia. However, no study has tested the reliability and validity of the MDAsin the Indonesian version, so it can be used effectively to assess dental anxiety among Indonesian population. Thisstudy aimed to determine the reliability and validity of the Indonesian version of MDAs. Analytic observational studywith cross sectional study was conducted in a patient population Dental Hospital Hasanuddin University that will beextracted, filled and scalled, with purposive sampling technique. Realibility of dental anxiety level was tested withCronbach's alpha test, the provision is acceptable if the value is >0.6.Using product moment correlation test, validity isaccepted if the value is >0.3. Results showed the questionnaire MDAS in Indonesian version has good internalconsistency with the value of 0.862, and a valid value (0.706). Based on the characteristics of the respondents, only agesignificantly affects anxiety level difference. It was concluded that the MDAS in Indonesian version has good reliability and validity.